A metabolomics approach to study the dual modulation by characterization of chemical alteration during processing of Gardeniae Fructus using UPLC-ESI-QTOF. Issue 17 (20th April 2016) - Li, Huan; Yang, Hong; Xue, Xuejia; Liu, Xiao; Tian, Feng; Poh, Yanhong; Cai, Hao; Lee, Yian Hoon; Yu, Hanry; Ong, Seng Poon; Cai, Baochang
Abstract : Dual modulation is an interesting phenomenon that may occur during Chinese Materia Medica processing whereby the crude and processed products have completely opposite therapeutic effects in vivo . Abstract : Dual modulation is an interesting phenomenon that may occur during Chinese Materia Medica (CMM) processing whereby the crude and processed products have completely opposite therapeutic effects in vivo due to chemical component alteration. Therefore, a comprehensive study of the chemical alteration in order to shed light on the reason behind dual modulation is of critical importance. Metabolomics employs an untargeted approach to obtain an overview on secondary metabolites in multi-component systems using high resolution LC-MS 2, which fulfills the requirement of a comprehensive analysis to clarify the mechanism of dual modulation. Gardeniae Fructus (GF), is one of the many widely used medicines across Asia, and its processed product exhibits completely opposite therapeutic effects on blood stasis. Therefore, we chose crude and processed GF to examine changes in secondary metabolites using UPLC-ESI-QTOF. In the subsequent chemometric analysis, both principal component analysis (PCA, unsupervised feature extraction) and orthogonal partial least-squares analysis (OPLSA, supervised feature extraction) were used to find out the chemical changes during processing. Iridoid Glycosides – jaminoside B, genipine-1-β-gentiobioside, 6α-hydroxygeniposide, and geniposide – and other ingredients such as mannitol and crocin were found to have decreased three to four fold in processed GF compared to crude GF, whereas another iridoid glycoside with a carboxyl group, mussaenosidic acid, was found to increase two fold in the processed product. This rapid yet reliable screening method can be also applied to other CMM to characterize the chemical changes and further explain the reasons behind dual modulation.